Effect of intra-arterial nimodipine on iatrogenic vasospasms during endovascular stroke treatment – angiographic resolution and infarct growth in follow-up imaging - Jessica Jesser; Arne Potreck; Dominik Vollherbst; Fatih Seker; Min Chen; Silvia Schönenberger; Thuy D. Do; Martin Bendszus; Markus A. Möhlenbruch; Charlotte S. Weyland (BMC Neurology, 2023)
Abstract Purpose The treatment of vasospasms during endovascular stroke treatment (EST) with intra-arterial nimodipine (NM) is routinely performed. However, the efficacy of resolving iatrogenic vasospasms during the angiographic intervention and the infarct development in follow-up imaging after EST has not been studied yet. Methods Retrospective single-center analysis of patients receiving EST for anterior circulation vessel occlusion between 01/2015 and 12/2021. The primary endpoint was ASPECTS in follow-up imaging. Secondary endpoints were the clinical outcome (combined endpoint NIHSS 24 h after EST and difference between modified Rankin Scale (mRS) before stroke and at discharge (delta mRS)) and intracranial hemorrhage (ICH) in follow-up imaging. Patients with vasospasms receiving NM (NM+) or not (NM-) were compared in univariate analysis. Results Vasospasms occurred in 79/1283 patients (6.2%), who consecutively received intra-arterial NM during EST. The targeted vasospasm angiographically resolved in 84% (66/79) under NM therapy. ASPECTS was lower in follow-up imaging after vasospasms and NM-treatment (NM – 7 (6–9), NM + 6 (4.5-8), p = 0.013) and the clinical outcome was worse (NIHSS 24 h after EST was higher in patients treated with NM (median, IQR; NM+: 14, 5–21 vs. NM-: 9, 3–18; p = 0.004), delta-mRS was higher in the NM + group (median, IQR; NM+: 3, 1–4 vs. NM-: 2, 1–2; p = 0.011)). Any ICH (NM+: 27/79, 34.2% vs. NM-: 356/1204, 29.6%; p = 0.386) and symptomatic ICH (NM+: 2/79, 2.5% vs. NM-: 21/1204, 1.7%; p = 0.609) was equally distributed between groups. Conclusion Intra-arterial nimodipine during EST resolves iatrogenic vasospasms efficiently during EST without increasing intracranial hemorrhage rates. However, patients with vasospasms and NM treatment show higher infarct growth resulting in lower ASPECTS in follow-up imaging.